IMPLEMENTASI METODE RAD PADA PERANCANGAN SISTEM MASJID PINTAR: STUDI KASUS MASJID AL-BUSTAMI - Yevi Grata Putra; Madona, Angga; Sutabri, Tata (Jurnal Komunikasi, 2024)
The AL Bustami Mosque in Bukit Baru Village, Palembang City, faces various challenges in conventional management which have an impact on operational efficiency and effectiveness. These challenges include managing prayer schedules, assigning officers, managing donations, congregation data, and managing energy which is still done manually. To overcome this problem, a technology-based smart system was introduced, aimed at automating and integrating various aspects of mosque management. This research uses the Rapid Application Development (RAD) method to design and implement a smart system involving Internet of Things (IoT) technology, cloud computing, and big data analytics. The research results show that this smart system has succeeded in increasing the regularity of prayer schedules, management efficiency of the Mosque Prosperity Council (DKM), transparency in donation management, and more efficient energy management. The system implementation also received positive feedback from end users, namely mosque administrators and congregants. Overall, the "Smart Mosque" project at the AL Bustami Mosque shows that the use of technology can significantly improve mosque management. This system can be a model for other mosques that want to improve operational efficiency and service to congregations through the adoption of similar technology. Recommendations for further development include feature enhancements, system security, training programs, and ongoing evaluation.